Highly efficient electrochemiluminescence from iridium(iii) complexes with 2-phenylquinoline ligand. Issue 4 (8th December 2014) - Zhou, Yuyang; Li, Wanfei; Yu, Linpo; Liu, Yang; Wang, Xiaomei; Zhou, Ming
Abstract : Bis-(methylated 2-phenylquinoline) iridium(iii ) complexes demonstrated the strongest ECL. Abstract : A series of cyclometalated iridium(iii ) complexes with 2-phenylquinoline ligand (1–4 ) were designed and synthesized, which were thoroughly investigated by the photophysics, electrochemistry, theoretical calculations and electrochemiluminescence (ECL). By incorporating methyl groups into the 2-phenylquinoline, the corresponding complexes2 and3 displayed lower oxidative potential and higher HOMO energy levels. Most importantly, compared with tris(2, 2′-bipyridyl)ruthenium(ii ) ([Ru(bipy)3 ] 2+ ), these iridium(iii ) complexes demonstrated more intense ECL in acetonitrile solutions.